DALIT AUTOBIOGRAPHIES: A TESTIMONY OF PLIGHT - Dutta, Brahma; Rajeshvari (ShodhKosh: Journal of Visual and Performing Arts, 2022)
All lives are important. Many of them can be penned down but only a few have the courage to indeed put them into words and make them public so that people can know the truth. Autobiography is a form of literature where in spite of writing about others, authors prefer to write their own life story. When there is a debate on Dalit Writings, dalit autobiographies are a much discussed topic. Even dalit authors being accused that they pen down their autobiographies along with one or two and they are seized to write further. But everyone has his own reason to adopt a particular form of writing. As Dalits always have been this complaint that their lives had never been considered worthy of narration or they would not be important enough to be the hero or protagonist of books authored by Swarnas. Eventually when education gave voice to them and power to pen they penned down the stories of their life to bring the truth to the world because they knew no one else would do that for them. Many autobiographies were written by Dalits. But some made a strong impact. ‘Jhootan’ written by Omprakash Valmiki is one of them.